STRATEGIES OF TRANSLATING ENGLISH IDIOMATIC EXPRESSIONS IN PAPER TOWNS INTO BAHASA INDONESIA BY ANGELIC ZAIZAI - Dwi Ismi Yulianti Pratiwi; Syahron Lubis (BAHAS, 2021)
Abstract This study discussed about the types of English idiomatic expressions in Paper Towns novel and how those idiomatic expressions are translated into Bahasa Indonesia. The data are collected from English and Bahasa Indonesia version of Paper Towns novel by John Green. This study used the theory by Fernando (1996) and Mona Baker (1992). There are 95 data collected and analyzed. (1) Three strategies are used in translating idiomatic expressions, 19 data are translated using an idiom of similar meaning and form, 6 data are translated using an idiom of similar meaning but dissimilar dorm and the mostly used strategy is translation by paraphrase with 70 data. Translation by omission does not applied by the translator. (2) Types of idiomatic expressions are find out, 14 data of literal idioms, 10 data of semi idioms, and the most commonly found is pure idiom with 71 data. Keywords: Idiomatic expressions, Types of idiom, Translation strategies